Monitoring the crime situation : a developing country perspective - Carranza, Elias...[et al.] (2006)
Draws on the experience of practitioners to suggest ways to establish effective crime data collection systems in developing countries. Highlights the importance of capacity-building, computerization and the technical support of the relevant international actors.